Effect of orthophosphate and calcium on the self assembly of concentrated sodium caseinate solutions. (January 2017) - Thomar, Peggy; Gonzalez-Jordan, Alberto; Dittmer, Jens; Nicolai, Taco
Abstract: The effect of orthophosphate (0–0.1 m ) on the aggregation of sodium caseinate in water (10–80 g L −1 ) induced by calcium ions was studied using confocal microscopy, sedimentation and 31 P magic angle spinning nuclear magnetic resonance spectroscopy. In the presence of calcium ions (0–0.1 m ), orthophosphate binds to the caseins leading to the formation of complexes involving all four types of casein. Above a critical molar calcium/protein ratio in the complex, large protein aggregates were formed that sedimented during centrifugation. The critical molar ratio increased from about 6 without added orthophosphate to about 10 in excess orthophosphate. Excess orthophosphate precipitated in the form of calcium phosphate particles and competed with caseins for binding of calcium ions. Binding of calcium ions led to immobilisation of inorganic orthophosphate and organic phophoserines in solid nanoparticles. In excess CaCl2 and orthophosphate, the complexes contained about 13 calcium and 10 orthophosphate ions.